FAMILY INDEPENDENCE IN PREVENTING STUNTING IN CHILDREN - Ni Putu Aryani; Baiq Ricca Afrida; Agus Supinganto (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Stunting di Kabupaten Lombok Barat masih tinggi kejadiannya.Status ekonomi dan pendidikan rendah sehingga kemampuan ibu dalam perawatan anak tidak baik. Perlunya peningkatan pengetahuan dalam perawatan anak Balita sehingga tumbuh kembang anak menjadi normal. Berdasarkan analisa situasi, permasalahan yang dihadapi mitra yaitu belum sepenuhnya mengetahui perawatan dan tumbuh kembang Balita.Tujuan pengabdian ini untuk (1) meningkatkan pengetahuan dalam upaya pencegahan masalah stunting pada Balita, (2) Memberikan pengetahuan kepada ibu mengenai perawatan Balita; (3) Meningkatkan keterampilan pengenalan gizi Balita. Metode yang digunakan dalam pengabdian ini berupa penyuluhan dan pendampingan dilakukan oleh tim pengabdian masyarakat dengan materi (1) Pengenalan tentang Stunting pada Balita; (2) Pengenalan tanda gizi kurang; (3) Pengenalan cara mengukur tinggi dan berat badan Balita. Mitra pengabdian ini yaitu Dusun Punikan Kecamatan Lingsar Kabupaten Lombok Barat. Jumlah peserta yang mengikuti penyuluhan dan pendampingan sebanyak 20 ibu yang mempunyai Balita dengan evaluasi berupa pre-test dan post-test. Hasil kegiatan menunjukkan 80% ibu telah mendapat pengetahuan dan wawasan tentang pencegahan Stunting dan perawatan Balita. Abstract: Stunting in West Lombok Regency is still high in incidence. Lack of economic status and low education so that the ability of mothers in child care is not good. It is necessary to increase the knowledge of mothers in the care of children under five so that the child's growth and development will be normal. Based on the situation analysis, the problems faced by the partners are that mothers do not fully understand the care and development of toddlers. The purpose of this service is to (1) increase knowledge of mothers in efforts to prevent stunting problems in toddlers, (2) provide knowledge to mothers about toddler care; (3) Improving the skills of mothers in the introduction of nutrition to children under five. The method used in this service is in the form of counseling and assistance carried out by the community service team with materials in the form of (1) Introduction to Stunting in Toddlers; (2) Recognition of signs of undernutrition; (3) Introduction of how to measure toddler's height and weight. This service partner is Punikan Hamlet, Lingsar District, West Lombok Regency. The number of participants who took part in the counseling and mentoring was 20 mothers who had toddlers with evaluations in the form of pre-test and post-test. The results of the activity show that 80% of mothers have received knowledge and insight about stunting prevention and toddler care.